2016
DOI: 10.1158/2326-6066.cir-15-0267
|View full text |Cite
|
Sign up to set email alerts
|

Anti–PD-1 Inhibitor–Related Pneumonitis in Non–Small Cell Lung Cancer

Abstract: The recent approval of two PD-1 inhibitors for the treatment of non–small cell lung cancer (NSCLC) has rapidly led to the widespread use of these agents in oncology practices. Pneumonitis has been recognized as a potentially life-threatening adverse event among NSCLC patients treated with PD-1 inhibitors; however, the detailed clinical and radiographic manifestations of this entity remain to be described. We report two cases of anti–PD-1 pneumonitis in advanced NSCLC patients treated with nivolumab after its F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 18 publications
4
115
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first case‐control study systematically seeking to identify risk factors for anti‐PD‐1 mAbs‐related pneumonitis development in a Chinese population of multiple types of advanced cancer. This study fills an important gap in the literature and supplements the limited number of published reports on anti‐PD‐1 pneumonitis 5, 16, 17, 18…”
Section: Discussionsupporting
confidence: 72%
“…To the best of our knowledge, this is the first case‐control study systematically seeking to identify risk factors for anti‐PD‐1 mAbs‐related pneumonitis development in a Chinese population of multiple types of advanced cancer. This study fills an important gap in the literature and supplements the limited number of published reports on anti‐PD‐1 pneumonitis 5, 16, 17, 18…”
Section: Discussionsupporting
confidence: 72%
“…A 58-year-old man developing NSIP radiological pattern after only 7 weeks of therapy. Other data is provided by Nishino et al who found that in a population of 170 patients treated with nivolumab, alone or in combination with other immune checkpoint inhibitors, 20 patients (11%) developed pneumonitis [7]. The international clinical trials concluded low risk of DILD after treatment with nivolumab, pembrolizumab and docetaxel [8][9][10][11][12], but these results will presumably prove to be underestimated after 2 years follow-up.…”
Section: Casementioning
confidence: 99%
“…The panorama of treatment options includes new immunotherapeutic drugs, approved for lung cancer therapy. These molecules enhance anti-tumor immunity by inhibiting negative T cell regulators and programmed cell-death-1 [4][5][6][7][8][9][10]. Immune checkpoint inhibitors currently approved for treatment of advanced NSCLC include nivolumab (anti CTLA-4 and anti PD1), pembrolizumab (anti PD1) and atezolizumab (anti PDL-1) [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no apparent relationship to tumor type treated, as pneumonitis cases have been observed in studies with multiple tumor types, including melanoma and lung and kidney cancers, although it has been suggested that pneumonitis presents more often when anti-PD-1 agents are used in patients with lung cancer than melanoma (39,43,44). Pneumonitis symptoms include cough, shortness of breath, dyspnea and fever and often involve only asymptomatic radiographic changes.…”
Section: Pneumonitismentioning
confidence: 99%